A numerical analysis of the biomechanics of the thoracolumbar spine and the effects of vertebral body tethering instrumentation - Oliveira, Rafael Carreira (2024)
Dissertação (mestrado) ? Universidade Federal de Santa Catarina, Centro Tecnológico, Programa de Pós-Graduação em Engenharia Mecânica, Florianópolis, 2024.